Assessment of the Cost of Illness Associated with Type 2 Diabetes - Chaitanya, G.; Nagasri, J.; Sravanhi, CH.; Thanuja, CH.; Adepu, Ramesh (Journal of Pharmacy Practice and Community Medicine, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder associated with significant clinical and economic burden worldwide. Diabetes increases preventable sickness and costs to healthcare and productivity. Type 2 diabetes and macrovascular consequences cause most diabetes-related costs. Type 2 diabetes imposes high costs on healthcare institutions, reducing economic productivity and efficiency. This Cost-of-Illness (COI) analysis examines the direct and indirect costs of treating and managing type 2 diabetes mellitus. Objectives: To estimate the Cost of Illness (COI) associated with T2DM management. Materials and Methods: A prospective, observational, prevalence-based cost-of-illness study was conducted in five diabetic clinics in Suryapet town, Telangana, over a 6-month period. A total of 100 patients with type 2 diabetes mellitus were enrolled. Direct medical and non-medical costs were calculated using a bottom-up micro-costing approach. Results: About 100 patients with type 2 diabetes were enrolled in the study. Among them were 50 males (30 with complications +20 without complications) and 50 females (33 with complications +17 without complications). The mean age of enrolled patients was 56.2 years, and the disease duration was 10.1±5.9 years. The annual cost per patient with complications was ₹44,417.68 (US$510.96) compared to ₹27,804.96 (US$319.68) for patients without complications. Medication and laboratory costs accounted for the largest share of direct costs. Regression analysis identified complications, insulin therapy and hospitalisation as major predictors of increased total cost. Conclusion: The economic burden of T2DM is substantial and increases significantly with complications. Strengthening preventive strategies, such as the presence of a clinical pharmacist in pharmacotherapeutic management, reduces out-of-pocket expenditure
Keywords: Bottom-up micro costing; Clinical pharmacist; Cost of illness; Direct cost; Indirect cost; Type 2 Diabetes Mellitus